Non-professional interpreters in counselling for asylum seeking and refugee women Filiz Celik, Tom Cheesman - Celik, Filiz; Cheesman, Tom (Torture Journal, 2018)
Introduction: Non-professional interpreting warrants further study, particularly in environments where professional interpreters are scarce. Method: The lead researcher (a qualified interpreter and counsellor) joined 32 group sessions as a participant observer, and 12 individual sessions as an observer. Additional data sources were 30 semi-structured interviews with counsellors, clients and interpreters, and two halfday forums organised for community interpreters to discuss their concerns. Results: The positive value of engaging non-professional interpreters is highlighted within the specific context of non-medical, community-based, holistic counselling. In this context, formal accuracy of translation is less important than empathy and trust. Non-professional interpreters may be more likely than professionals to share clients’ life experiences, and working with them in counselling has positive psychosocial value for all participants. This is because it entails inclusive, non-hierarchical practices in the client-counsellor-interpreter triad: mutual sharing of linguistic resources and translingual communication, and a more relaxing dynamic with fluid roles. In group sessions, a strong sense of a crosslinguistic community is created as women interpret for one another, an expression of mutual support. In the context of this study, counsellors, clients and interpreters alike all regard non-professionals as being more appropriate than professionals in most counselling situations.